Non-invasive in vivo imaging of brain and retinal microglia in neurodegenerative diseases - Etebar, Fazeleh; Harkin, Damien G.; White, Anthony R.; Dando, Samantha J. (Frontiers in Cellular Neuroscience, 2024)
Microglia play crucial roles in immune responses and contribute to fundamental biological processes within the central nervous system (CNS). In neurodegenerative diseases, microglia undergo functional changes and can have both protective and pathogenic roles. Microglia in the retina, as an extension of the CNS, have also been shown to be affected in many neurological diseases. While our understanding of how microglia contribute to pathological conditions is incomplete, non-invasive in vivo imaging of brain and retinal microglia in living subjects could provide valuable insights into their role in the neurodegenerative diseases and open new avenues for diagnostic biomarkers. This mini-review provides an overview of the current brain and retinal imaging tools for studying microglia in vivo. We focus on microglia targets, the advantages and limitations of in vivo microglia imaging approaches, and applications for evaluating the pathogenesis of neurological conditions, such as Alzheimer's disease and multiple sclerosis.